ADAPTING WEB ELECTRONIC LIBRARIES TO ENGLISH STUDIES - Douglas, Christopher; Jerz, Dennis; Lancashire, Ian (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1999)
University of Toronto's Department of English developed UTEL, a teaching and research World Wide Web site designed to foreground the diverse theoretical and methodological approaches in that department's views on literature. We argue that academia needs to build local academic content into electronic libraries by supplying faculty essays, notes, lecture materials, and dedicated databases, all selected and created to mirror the specific purposes and identities of the academics who will use it. Doing so requires a long-term institutional infrastructure with peer review, and coherent goals — a model not found in individual or commercial Web collections, in purely administrative departmental sites, or on the World Wide Web itself.